2018
DOI: 10.1155/2018/4201325
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chinese Herbal Medicine Improves Chemotherapy‐Induced Thrombocytopenia among Gynecological Cancer Patients: An Observational Study

Abstract: Background Chemotherapy-induced thrombocytopenia (CIT) is a serious complication among patients with gynecological malignancies, yet management options are limited. This study aimed at reporting the potential of the Chang Gung platelet elevating formula (CGPEF), a prescription with a fixed proportion of Chinese herbs, for improving CIT among gynecologic cancer patients. Materials From 1/1/2007 to 31/12/2009, a total of 23 patients with two consecutive CIT episodes (≤ 100×103 /μL) (last cycle: C0; index cycle: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The chemoradiotherapy regimens commonly used to treat OC often cause serious adverse effects, which severely affect the QoL and immune function of patients. [ 17 – 21 ] Therefore, seeking an alternative therapy that can improve the QoL and immune function of patients is urgently required for tumor treatment. Several studies have recognized that TCM have a unique advantage in the treatment of malignant tumors by inhibiting the growth of cancer cells, enhancing immunity of human body, decreasing cancer relapses and metastases, and mitigating the progress of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemoradiotherapy regimens commonly used to treat OC often cause serious adverse effects, which severely affect the QoL and immune function of patients. [ 17 – 21 ] Therefore, seeking an alternative therapy that can improve the QoL and immune function of patients is urgently required for tumor treatment. Several studies have recognized that TCM have a unique advantage in the treatment of malignant tumors by inhibiting the growth of cancer cells, enhancing immunity of human body, decreasing cancer relapses and metastases, and mitigating the progress of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recognized that TCM have a unique advantage in the treatment of malignant tumors by inhibiting the growth of cancer cells, enhancing immunity of human body, decreasing cancer relapses and metastases, and mitigating the progress of the disease. [ 17 – 21 , 32 – 38 ] Piao et al [ 21 ] found that complementary treatment with mistletoe extracts can beneficially reduce the side effects of chemotherapy and thus improve QoL of patients with breast, ovarian and nonsmall cell lung cancer. Research by Chan et al [ 18 ] indicated that TCM did not improve QoL of cancer patients but did have some effects in terms of maintaining immune function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, the use of Traditional Chinese medicine (TCM)-based CHM for breast cancer has been described for more than 2,000 years in China by TCM physicians (10,11). It is considered that CHM shows the potency to alleviate the toxicities of chemotherapy agents and control the side-effects, such as improves the patient's quality of life (QoL), prevents recurrence, and prolongs survival (12)(13)(14)(15). Therefore, we performed this systematic review and metaanalysis to evaluate the efficacy of CHM as an adjunctive therapy to reduce side-effect of chemotherapy for breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] In addition, CHMs or their related natural compounds exhibit beneficial effects against ovarian cancer by enhancing cancer cell apoptosis, reducing multidrug resistance, or alleviating complications of regular treatment. [20][21][22][23] Thus far, there have been no clinical treatments using CHM for patients with ovarian cancer; therefore, its clinical efficacy and overall survival rate need to be investigated. The association between CHM prescription patterns with increased survival rates in patients with ovarian cancer remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%